Una fine mancata - innovazione o imperfezione? - Chmiel, Aneta (Romanica Silesiana)
Aneta Chmiel shows the places semantically unspecified in a poem by Teofil Folengo Baldus. Keywords: semantic indeterminacy; Italian poetry; Teofil Folengo